Incidencia de las tasas de interés en la rentabilidad de las cooperativas de ahorro y crédito, segmento 1 y 2 de la ciudad de Loja - Collaguazo Agila, Rosa Thalia (2023)
Savings and credit cooperatives are the key to the country's economic development. The objective of the present research work was to analyze the impact of interest rates on the profitability of segment 1 and 2 credit unions in Loja city. For this purpose, a mixed approach was used, which included a detailed description of the evolution of interest rates, considering their fluctuations, and the analysis of the financial indicators of credit unions, such as return on equity and return on assets. Changes over the study period were examined, which made it possible to identify trends in the profitability of the institutions. In addition, Pearson's correlation was used to evaluate whether there is a significant relationship between interest rates and profitability. The study population consisted of ten savings and loan cooperatives in segments one and two operating in Loja. The results of the study show that interest rates vary due to factors such as inflation, country risk and monetary policy. In addition, it was determined that there is a very low negative relationship between interest rates and profitability indicators (ROA and ROE) of segment one credit unions. As for segment two credit unions, a low relationship was found between interest rates and ROA, while the relationship between interest rates and ROE was high positive. Therefore, it is concluded that the profitability generated by the entities depends to a greater extent on interest rates.